A nanofiltration membrane based on crown ether modified MOF channels and a preparation method thereof

CN122912700APending Publication Date: 2026-10-16WUHAN UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611414493.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-11
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

然而,单一MOF在此过程中本质上仍属静态的尺寸截留,缺乏对特定离子的动态识别能力,对于多离子混合体系仍难以实现高效截留

Benefits of technology

(1)本发明针对不同离子的截留需求,依据被截留离子水合离子半径大小与配位特性选择适配的冠醚分子,并将其作为识别位点嵌入MOF-A的孔道中,具有高度特异空腔结构的冠醚分子能够基于主客体识别机制选择性结合特定的金属阳离子,从而构建具有对客体离子识别能力的MOF(CE)结构。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122912700A_ABST
    Figure CN122912700A_ABST
Patent Text Reader

Abstract

The application relates to the technical field of functional film materials, in particular to a nanofiltration membrane based on crown ether modified MOF channels and a preparation method thereof. The nanofiltration membrane comprises an alumina film substrate, a seed layer, a MOF-A layer with crown ether embedded channels and a MOF-B layer, and forms a MOF-on-MOF composite structure. In the preparation, the seed layer is first formed on the substrate, then the high-valence metal compound, the first organic ligand and the crown ether are mixed for in-situ growth, the crown ether is synchronously embedded into the MOF-A channel, and then the MOF-B layer is deposited, and each MOF layer is deposited twice. According to the application, the MOF-B layer retains divalent metal cations, the crown ether modified MOF-A layer accurately identifies and retains monovalent metal cations, the cascade retention of 'first two and then one' is realized, the retention rate of the monovalent metal cations reaches more than 95%, and the retention rate of the divalent metal cations reaches more than 99%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of functional membrane materials technology, specifically to a nanofiltration membrane based on crown ether-modified MOF pores and its preparation method. Background Technology

[0002] Nanofiltration, as a highly efficient, energy-saving, and flexible membrane separation technology, has been widely used in seawater desalination and resource extraction due to its ability to achieve differentiated filtration at the molecular scale. It primarily relies on pore size to retain ions. However, most existing nanofiltration membranes are polymeric membranes, which suffer from uneven pore size distribution, resulting in limited ion retention efficiency when processing mixed systems with multiple valence states.

[0003] Metal-organic frameworks (MOFs), as porous materials formed by metal nodes and organic ligands, have a core advantage in the tunability of their organic ligands, enabling the retention of metal cations based on the pore size of the MOF. However, a single MOF in this process is essentially still a static size-based retention method, lacking the ability to dynamically recognize specific ions, and still struggling to achieve efficient retention in multi-ion mixed systems.

[0004] Given the lack of dynamic recognition of specific ions in single MOFs, crown ethers (CEs), with their highly specific cavity structure, can selectively bind metal cations based on a host-guest recognition mechanism. The oxygen atoms on their rings act as coordination sites, forming stable coordination bonds with size-matched metal cations, thus achieving the recognition of guest monovalent metal cations. Embedding crown ethers into the MOF cavity as recognition sites utilizes their ion recognition capabilities to achieve efficient retention of monovalent metal cations. However, according to the research in the literature "Perfect confinement of crown ethers in MOF membrane for completedehydration and fast transport of monovalent ions," it can be seen that the retention rate of monovalent metal cations in single MOF plus crown ether materials is not high. + Permeability as high as 1.2 mol·m -2 ·h -1 .

[0005] Therefore, there is an urgent need to develop a nanofiltration membrane and its preparation method that can synergistically utilize the MOF size sieving effect and crown ether host-guest recognition mechanism to have a graded retention capacity for monovalent and divalent metal cations. Summary of the Invention

[0006] In view of this, the present invention provides a nanofiltration membrane based on crown ether-modified MOF channels and its preparation method. By embedding crown ethers into the channels of MOFs as recognition sites, specific metal cations are effectively recognized and stable coordinate bonds are formed with them, locking the ions in the cavities of the MOF. Furthermore, a MOF-on-MOF structure is introduced, with MOF-B deposited on the surface of MOF-A crystals, constructing a MOF-on-MOF nanofiltration membrane with multi-level retention channels for metal cations. The interaction between the size of the MOF and the host-guest recognition mechanism of the crown ether enhances the retention rate of metal cations with different valence states. The two MOF layers work synergistically, achieving a retention rate of over 95% for monovalent metal cations and over 99% for divalent metal cations.

[0007] The technical solution of this invention is implemented as follows: In a first aspect, the present invention provides a nanofiltration membrane based on crown ether-modified MOF channels, the nanofiltration membrane comprising: Alumina film (AAO) substrate; A seed layer is disposed on the surface of the AAO substrate; The MOF-A layer disposed on the surface of the seed layer is composed of a high-valence metal compound and a first organic ligand, and crown ether molecules are embedded in the pores of the MOF-A layer. The MOF-B layer is disposed on the surface of the MOF-A layer, and the MOF-B layer is composed of a low-valence metal compound and a second organic ligand.

[0008] Specifically, the MOF formed by the low-valence metal compound is used only for the physical interception of divalent metal cations, while the MOF formed by the high-valence metal compound is used for the intercalation of crown ethers.

[0009] Preferably, the thickness of the seed layer is 1~3 μm, the thickness of the MOF-A layer is 4~10 μm, and the thickness of the MOF-B layer is 3~6 μm.

[0010] Specifically, the seed layer provides a uniform and stable interface for the subsequent deposition and growth of MOFs, ensuring that the MOFs can completely cover the surface of the AAO membrane. The MOF-A layer provides ample space for the embedding of crown ether molecules, increasing the crown ether loading, and its greater thickness can improve the mechanical strength of the membrane, stably supporting the upper MOF-B layer. The MOF-B layer mainly undertakes the physical retention of divalent metal cations; while ensuring retention efficiency, flux must also be considered, therefore the thickness of the MOF-B layer needs to be moderate.

[0011] Preferably, the high-valence metal compound includes one or more of zirconium propoxide, zirconium nitrate, zirconium chloride, titanium chloride, hafnium tetrachloride, zirconium acetylacetonate, titanium isopropoxide, titanium tetramethoxy, and hafnium dichloride; the low-valence metal compound includes one or more of zinc nitrate, cobalt nitrate, nickel nitrate, copper nitrate, ferric nitrate, zinc chloride, cobalt chloride, nickel chloride, copper chloride, ferric chloride, zinc acetylacetonate, cobalt acetylacetonate, nickel acetylacetonate, copper acetylacetonate, and iron acetylacetonate.

[0012] Preferably, the first organic ligand comprises one or more of benzoic acid, o-methylbenzoic acid, m-methylbenzoic acid, p-methylbenzoic acid, phthalic acid, isophthalic acid, terephthalic acid, o-ethylbenzoic acid, m-ethylbenzoic acid, p-ethylbenzoic acid, 2-aminoterephthalic acid, and 2-amino-1,4-phthalic acid; and the second organic ligand comprises one or more of imidazole, 1-methylimidazolium, 2-methylimidazolium, 4-methylimidazolium, 1,2-dimethylimidazolium, benzimidazole, 2-methylbenzimidazole, and 2-phenylbenzimidazole.

[0013] Preferably, the crown ether comprises one or more of 12-crown-4, 15-crown-5, 18-crown-6, 24-crown-8, benzo-12-crown-4, benzo-15-crown-5, benzo-18-crown-6, benzo-21-crown-7, dibenzo-15-crown-5, dibenzo-18-crown-6, dibenzo-21-crown-7, dibenzo-24-crown-8, dibenzo-30-crown-10, 4-carboxybenzo-15-crown-5, and 4-carboxybenzo-18-crown-6.

[0014] Preferably, the MOF-A layer comprises UiO-66, the MOF-B layer comprises ZIF-67 or ZIF-8, and the crown ether comprises one or more of 12-crown-4, 15-crown-5, 18-crown-6, benzo-18-crown-6, dibenzo-15-crown-5, and dibenzo-18-crown-6.

[0015] In a second aspect, the present invention provides a method for preparing a nanofiltration membrane based on crown ether-modified MOF pores as described in the first aspect, comprising the following steps: S1. Pre-treat AAO by placing it in an N,N-dimethylformamide solution containing the first organic ligand to form a seed layer on the surface of AAO. S2. Mix and dissolve the high-valence metal compound, the first organic ligand and the crown ether, and grow it in situ on the AAO surface treated by S1 to deposit the MOF-A layer and make the crown ether molecules synchronously embedded in the pores of the MOF-A layer. S3. Repeat step S2 once to complete the secondary deposition of the MOF-A layer and the secondary intercalation of the crown ether; S4. Mix and dissolve the low-valence metal compound with the second organic ligand, and deposit a MOF-B layer on the surface of the film obtained in S3; S5. Repeat step S4 once to complete the secondary deposition of the MOF-B layer and obtain the nanofiltration membrane based on crown ether modified MOF channels.

[0016] Preferably, in step S2, the mass ratio of the high-valence metal compound, the first organic ligand, and the crown ether is 1:(1-3):(1.8-5).

[0017] Preferably, in step S2, the deposition temperature is 25~35 ℃ and the deposition time is 12~24 h; in step S4, the deposition temperature is 25~35 ℃ and the deposition time is 1~2 h.

[0018] Preferably, in step S1, the pretreatment temperature is 110~140 ℃ and the pretreatment time is 1~3 h.

[0019] Thirdly, the present invention provides an application of the nanofiltration membrane described in the first aspect in separating a mixed liquid containing monovalent metal cations and divalent metal cations.

[0020] Compared with the prior art, the advantages of the present invention are as follows: (1) In view of the different ion retention requirements, the present invention selects suitable crown ether molecules according to the size of the hydrated ion radius and coordination characteristics of the retained ion, and embeds them as recognition sites into the pores of MOF-A. The crown ether molecules with highly specific cavity structure can selectively bind specific metal cations based on the host-guest recognition mechanism, thereby constructing an MOF (CE) structure with the ability to recognize guest ions.

[0021] (2) In view of the ion retention requirements in different systems, this invention constructs a MOF-on-MOF nanofiltration membrane with multi-stage retention channels for various mixed systems by controlling the types of metal compounds and organic ligands. The membrane retains divalent metal cations with larger radii outside, and then uses crown ether to retain monovalent metal cations in the crown ether cavity, forming a "two-stage first, one-stage later" cascade retention. The two stages of retention are seamlessly connected, resulting in a composite nanofiltration membrane with high retention performance.

[0022] (3) This invention utilizes the synergistic effect of the double-layer MOF structure. The combined action of MOF-A and MOF-B can retain a large number of divalent metal cations through simple physical separation. The subsequent crown ether retains monovalent metal cations as a pretreatment, reducing the number and type of ions recognized by the crown ether molecule, and making the retention of monovalent metal cations more accurate.

[0023] (4) The present invention uses an in-situ synthesis method to grow MOF on a substrate without high pressure and high temperature. The synthesis process consumes less energy, the MOF-on-MOF structure is stable, the rejection rate of metal cations is high, the method is simple to operate, and the processing cycle is short. Attached Figure Description

[0024] Figure 1 Lateral scanning electron microscope image of the process of preparing UiO-66 (DB18C6) in Example 1; Figure 2 A longitudinal scanning electron microscope image of the UiO-66(DB18C6)@ZIF-8 nanofiltration membrane prepared in Example 1; Figure 3 XRD patterns of UiO-66 (DB18C6) and UiO-66; Figure 4 The XRD pattern of ZIF-8; Figure 5 XPS images of the process of preparing UiO-66 (DB18C6) in Example 1; Figure 6 XPS image of the UiO-66(DB18C6)@ZIF-8 nanofiltration membrane prepared in Example 1; Figure 7 The desalination rate of the UiO-66(DB18C6)@ZIF-8 nanofiltration membrane prepared in Example 1 in a mixed system of the same valence states; Figure 8 The ion desalination rate of the UiO-66(DB18C6)@ZIF-8 nanofiltration membrane prepared in Example 1 in different valence state mixed systems; Figure 9 Thermogravimetric curves of UiO-66 (DB18C6), UiO-66, and DB18C6; Figure 10 BET adsorption-desorption curves of UiO-66 (DB18C6) and UiO-66; Figure 11 The UiO-66(DB18C6)@ZIF-8 nanofiltration membrane prepared for Example 1 was used in K + / Na + IV curve of the system; Figure 12 The UiO-66(DB18C6)@ZIF-8 nanofiltration membrane prepared in Example 1 was used in Li + / Na + IV curve of the system; Figure 13 The UiO-66(DB18C6)@ZIF-8 nanofiltration membrane prepared in Example 1 was used in Li + / Mg 2+IV curve of the system; Figure 14 The UiO-66(DB18C6)@ZIF-8 nanofiltration membrane prepared for Example 1 was used in Na + / Mg 2+ IV curve of the system; Figure 15 The UiO-66(DB18C6)@ZIF-8 nanofiltration membrane prepared for Example 1 was used in K + / Mg 2+ IV curve of the system; Figure 16 The UiO-66(DB18C6)@ZIF-8 nanofiltration membrane prepared for Example 1 was used in K + / Ca 2+ IV curve of the system. Detailed Implementation

[0025] Embodiments of the present invention are described in detail below, examples of which are illustrated in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and intended to explain the present invention, and should not be construed as limiting the present invention.

[0026] In the MOF preparation process, different types of MOFs are synthesized by adding different metal compounds. Different types of crown ethers are inserted for different ions to grow two different MOFs. The main purpose of depositing each MOF material twice is to reduce the formation of defects and to enable each layer of MOF material to form a uniform and intact crystal structure, thereby constructing a MOF-on-MOF (CE) nanofiltration membrane with gradient pore size.

[0027] The key technical challenge of this invention is regulating the retention process of metal ions with different valence states in a mixed system. Inspired by channel proteins on cell membranes in living organisms, which contain ion channels and ion binding sites, this invention simulates a biomimetic process, using MOF pores as ion channels and crown ethers as ion binding sites. Based on the size and coordination characteristics of the retained metal ions, suitable crown ether molecules and high-valence metal compounds are selected to form MOF-A, constructing biomimetic ion recognition sites. Furthermore, mimicking the bilayer structure of cell membranes, by using different organic ligands and metal compounds with different valence states, the time and temperature of the deposition process are controlled to construct MOF-on-MOF (CE) nanofiltration membranes with multi-level retention channels of different pore sizes.

[0028] Most metal ions are removed through a "two-first, one-second" retention process. The process begins with divalent metal cations with larger hydration radii passing through the MOF-B layer. Because their hydration radii are larger than the pore size of MOF-B, most divalent ions are retained. A small number of divalent and monovalent metal cations pass through the MOF-B layer to the MOF-A layer. Ions with hydration radii larger than the pore size of MOF-A are also retained. Smaller monovalent metal cations then enter the MOF-A cavity. Since ions must be completely exposed to pass through the crown ether, and complete dehydration requires a large amount of energy, metal cations recognized by the crown ether have a strong chemical affinity, compensating for the energy required for dehydration. After complete dehydration, they rehydrate on the other side of the crown ether. Metal cations that cannot be recognized cannot overcome the energy barrier during dehydration and therefore cannot pass through the crown ether. Therefore, a large number of metal cations that cannot be recognized by crown ethers cannot pass through the MOF-A layer. The two MOF layers work together to retain cations with large hydration radii. The MOF-A interacts with the crown ether to retain most of the monovalent metal cations, resulting in a large number of monovalent / divalent cations being retained.

[0029] It should be noted that the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of indicated technical features. Therefore, a feature defined as "first" or "second" may explicitly or implicitly include one or more of that feature. Furthermore, in the description of this invention, unless otherwise stated, "a plurality of" means two or more.

[0030] In this document, the terms “containing,” “comprising,” or “including” are open-ended expressions, meaning they include the contents specified in this invention but do not exclude other aspects.

[0031] In this document, the terms “optional,” “optionally,” or “optional” generally refer to an event or condition that may, but may not, occur, and the description includes both cases in which the event or condition occurs and cases in which the event or condition does not occur.

[0032] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the protection scope of the present invention.

[0033] Unless otherwise specified, all raw materials used in this invention are commercially available, and all purchased chemicals are used directly without purification. Specifically, the alumina membrane (AAO, pore size 0.2 μm, diameter 25 mm, thickness 60 μm) was purchased from Whatman Company, zirconium propoxide was purchased from Aladdin Reagent Co., Ltd., terephthalic acid, 1-propanol, acetic acid, 2-methylimidazole, polyvinylpyrrolidone, Zn(NO3)2·6H2O were purchased from Aladdin Reagent Co., Ltd., and dibenzo-18-crown-6, benzo-12-crown-4, benzo-18-crown-6, and 18-crown-6 were purchased from Aladdin Reagent Co., Ltd.

[0034] Example 1 This embodiment provides a UiO-66 (DB18C6)@ZIF-8 nanofiltration membrane with pores modified by dibenzo-18-crown-6 (DB18C6) and its preparation method, including the following steps: (1) Add 0.53 g terephthalic acid and 15 ml DMF to a glass bottle, sonicate until the terephthalic acid is completely dissolved, transfer the solution to a beaker, place AAO in the solution, and let it stand at 130 °C for 2.5 h to form a 2 μm seed layer on the surface of AAO for growing MOF film, thus achieving the pretreatment of AAO.

[0035] (2) Dissolve 500 μl of 70 wt% zirconium propoxide, 0.36 g of 1-propanol and 28 ml of acetic acid in 50 ml of DMF and heat at 130 °C for 2 h until a yellow solution is observed. After the solution is gradually cooled to room temperature, add 0.53 g of terephthalic acid and 1.1 g of DB18C6 (the mass ratio of zirconium propoxide, terephthalic acid and DB18C6 is 1:1.5:3.2). Place the pretreated AAO in the mixed solution and let it stand at 30 °C for 24 h for deposition. After taking out the film, rinse it three times with DMF. Then repeat the above deposition process once to achieve secondary growth of UiO-66 layer and re-intercalation of DB18C6. The resulting UiO-66 layer is 8 μm thick.

[0036] (3) Dissolve 1.132 g of 2-methylimidazole in 18 mL of deionized water, add 0.0136 g of polyvinylpyrrolidone (PVP) and dissolve it, then dissolve 0.054 g of Zn(NO3)2·6H2O in 2 mL of water. After quickly mixing the two solutions, immediately immerse the membrane obtained in step (2) into the mixture and let it stand at 30°C for 1.2 h to allow ZIF-8 to be deposited on the surface of UiO-66. After removing the membrane, repeat the deposition process once. The thickness of the obtained ZIF-8 layer is 4 μm, and a UiO-66(DB18C6)@ZIF-8 nanofiltration membrane is obtained.

[0037] (4) The synthesized UiO-66(DB18C6)@ZIF-8 nanofiltration membrane was stored in anhydrous ethanol solution.

[0038] Example 2

[0039] This embodiment provides a method for preparing a UiO-66(B12C4)@ZIF-8 nanofiltration membrane with pores modified by benzo-12-crown-4 (B12C4): Step (1) is the same as in Example 1.

[0040] In step (2), DB18C6 is replaced with an equimolar amount of B12C4 (0.673 g), and the other conditions are the same as in Example 1.

[0041] Step (3) is the same as in Example 1.

[0042] Step (4) is the same as in Example 1, and a UiO-66(B12C4)@ZIF-8 nanofiltration membrane is obtained.

[0043] Example 3

[0044] This embodiment provides a method for preparing a UiO-66(B18C6)@ZIF-8 nanofiltration membrane with pores modified by benzo-18-crown-6 (B18C6): Step (1) is the same as in Example 1.

[0045] In step (2), DB18C6 is replaced with an equimolar amount of B18C6 (0.937 g), and the other conditions are the same as in Example 1.

[0046] Step (3) is the same as in Example 1.

[0047] Step (4) is the same as in Example 1, and a UiO-66(B18C6)@ZIF-8 nanofiltration membrane is obtained.

[0048] Example 4

[0049] This embodiment provides a method for preparing a UiO-66(18C6)@ZIF-8 nanofiltration membrane containing 18-crown-6 (18C6) modified pores: Step (1) is the same as in Example 1.

[0050] In step (2), DB18C6 is replaced with an equimolar amount of 18C6 (0.793 g), and the other conditions are the same as in Example 1.

[0051] Step (3) is the same as in Example 1.

[0052] Step (4) is the same as in Example 1, and a UiO-66(18C6)@ZIF-8 nanofiltration membrane is obtained.

[0053] Example 5

[0054] This embodiment provides a UiO-66 (DB18C6)@ZIF-8 nanofiltration membrane with pores modified by dibenzo-18-crown-6 (DB18C6) and its preparation method, including the following steps: (1) Add 0.36 g terephthalic acid and 15 ml DMF to a glass bottle, sonicate until the terephthalic acid is completely dissolved, transfer the solution to a beaker, place AAO in the solution, and let it stand at 110 °C for 1 h to form a 1 μm seed layer on the surface of AAO for growing MOF film, thus achieving the pretreatment of AAO.

[0055] (2) Dissolve 500 μl of 70 wt% zirconium propoxide, 0.36 g of 1-propanol and 28 ml of acetic acid in 50 ml of DMF and heat at 130 °C for 2 h until a yellow solution is observed. After the solution is gradually cooled to room temperature, add 0.36 g of terephthalic acid and 0.9 g of DB18C6 (the mass ratio of zirconium propoxide, terephthalic acid and DB18C6 is 1:1:2.5). Place the pretreated AAO in the mixed solution and let it stand at 25 °C for 12 h for deposition. After taking out the film, rinse it three times with DMF. Then repeat the above deposition process once to achieve secondary growth of UiO-66 layer and re-intercalation of DB18C6. The resulting UiO-66 layer is 4 μm thick.

[0056] (3) Dissolve 1.132 g of 2-methylimidazole in 18 mL of deionized water, add 0.0136 g of polyvinylpyrrolidone (PVP) and dissolve it, then dissolve 0.054 g of Zn(NO3)2·6H2O in 2 mL of water. After quickly mixing the two solutions, immediately immerse the membrane obtained in step (2) into the mixture and let it stand at 25 °C for 1 h to allow ZIF-8 to be deposited on the surface of UiO-66. After removing the membrane, repeat the deposition process once. The thickness of the ZIF-8 layer obtained is 3 μm, and UiO-66(DB18C6)@ZIF-8 nanofiltration membrane is obtained.

[0057] (4) The synthesized UiO-66(DB18C6)@ZIF-8 nanofiltration membrane was stored in an ethanol solution.

[0058] Example 6

[0059] This embodiment provides a UiO-66 (DB18C6)@ZIF-8 nanofiltration membrane with pores modified by dibenzo-18-crown-6 (DB18C6) and its preparation method, including the following steps: (1) Add 1.08 g of terephthalic acid and 15 ml of DMF to a glass bottle, sonicate until the terephthalic acid is completely dissolved, transfer the solution to a beaker, place AAO in the solution, and let it stand at 140 °C for 3 h to form a 3 μm seed layer on the surface of AAO for growing MOF film, thus achieving the pretreatment of AAO.

[0060] (2) Dissolve 500 μl of 70 wt% zirconium propoxide, 0.36 g of 1-propanol and 28 ml of acetic acid in 50 ml of DMF and heat at 130 °C for 2 h until a yellow solution is observed. After the solution is gradually cooled to room temperature, add 1.08 g of terephthalic acid and 1.8 g of DB18C6 (the mass ratio of zirconium propoxide, terephthalic acid and DB18C6 is 1:3:5). Place the pretreated AAO in the mixed solution and let it stand at 35 °C for 24 h for deposition. After taking out the film, rinse it three times with DMF. Then repeat the above deposition process once to achieve secondary growth of UiO-66 layer and re-intercalation of DB18C6. The resulting UiO-66 layer is 10 μm thick.

[0061] (3) Dissolve 1.132 g of 2-methylimidazole in 18 mL of deionized water, add 0.0136 g of polyvinylpyrrolidone (PVP) and dissolve it, then dissolve 0.054 g of Zn(NO3)2·6H2O in 2 mL of water. After quickly mixing the two solutions, immediately immerse the membrane obtained in step (2) into the mixture and let it stand at 35 °C for 2 h to allow ZIF-8 to be deposited on the surface of UiO-66. After removing the membrane, repeat the deposition process once. The thickness of the ZIF-8 layer obtained is 6 μm, and UiO-66(DB18C6)@ZIF-8 nanofiltration membrane is obtained.

[0062] (4) The synthesized UiO-66(DB18C6)@ZIF-8 nanofiltration membrane was stored in an ethanol solution.

[0063] Comparative Example 1

[0064] This comparative example provides a method for preparing a crown ether-free UiO-66@ZIF-8 nanofiltration membrane.

[0065] Step (1) is the same as in Example 1.

[0066] In step (2), no crown ether molecules were added, only 0.53 g of terephthalic acid was added, and the remaining conditions were the same as in Example 1, and deposition was performed twice.

[0067] Step (3) is the same as in Example 1.

[0068] Step (4) is the same as in Example 1, and a UiO-66 @ ZIF-8 nanofiltration membrane is obtained.

[0069] Comparative Example 2

[0070] This comparative example provides a method for preparing a single UiO-66 nanofiltration membrane.

[0071] Step (1) is the same as in Example 1.

[0072] In step (2), no crown ether molecules are added, only 0.53 g of terephthalic acid is added, and UiO-66 is deposited twice.

[0073] No step (3) is performed, and ZIF-8 deposition is not carried out.

[0074] Step (4) is the same as in Example 1, and a single UiO-66 nanofiltration membrane is obtained.

[0075] Comparative Example 3

[0076] This comparative example provides a method for preparing a single UiO-66 (DB18C6) nanofiltration membrane containing DB18C6 modified pores.

[0077] Step (1) is the same as in Example 1.

[0078] Step (2) is the same as in Example 1 (containing DB18C6, deposited twice).

[0079] No step (3) is performed, and ZIF-8 deposition is not carried out.

[0080] Step (4) is the same as in Example 1, resulting in a single UiO-66 (DB18C6) nanofiltration membrane.

[0081] Comparative Example 4

[0082] This comparative example provides a method for preparing a single ZIF-8 nanofiltration membrane.

[0083] In step (1), the AAO membrane was placed in 15 mL of deionized water containing 0.53 g of 2-methylimidazole and pretreated at 130 °C for 2.5 h.

[0084] No step (2).

[0085] In step (3), 1.132 g of 2-methylimidazole was dissolved in 18 mL of deionized water, 0.0136 g of PVP was added and dissolved, and then mixed with 2 mL of aqueous solution of 0.054 g of Zn(NO3)2·6H2O. The pretreated AAO membrane was then immersed in the mixture and allowed to stand for 1 h. The deposition was repeated twice.

[0086] Step (4) is the same as in Example 1, and a single ZIF-8 nanofiltration membrane is obtained.

[0087] Comparative Example 5

[0088] This comparative example provides a method for preparing a UiO-66(DB18C6)@ZIF-8 nanofiltration membrane with a UiO-66(DB18C6) layer deposited only once.

[0089] Step (1) is the same as in Example 1.

[0090] Step (2) involves only one deposition of UiO-66 (DB18C6). The remaining steps are the same as in Example 1, but only one deposition is performed, without a second deposition.

[0091] Step (3) is the same as in Example 1.

[0092] Step (4) is the same as in Example 1, resulting in a UiO-66(DB18C6)@ZIF-8 nanofiltration membrane with a UiO-66(DB18C6) layer deposited only once.

[0093] Comparative Example 6

[0094] This comparative example provides a method for preparing a UiO-66(DB18C6)@ZIF-8 nanofiltration membrane with a ZIF-8 layer deposited only once.

[0095] Step (1) is the same as in Example 1.

[0096] Step (2) is the same as in Example 1.

[0097] Step (3) involves only one ZIF-8 deposition and no second deposition.

[0098] Step (4) is the same as in Example 1, resulting in a UiO-66 (DB18C6)@ZIF-8 nanofiltration membrane with a ZIF-8 layer deposited only once.

[0099] Comparative Example 7

[0100] This comparative example provides a method for preparing a UiO-66(DB18C6)@ZIF-8 nanofiltration membrane with low crown ether content.

[0101] Step (1) is the same as in Example 1.

[0102] In step (2), DB18C6 is replaced with a low molar amount of DB18C6 (0.36 g), and the other conditions are the same as in Example 1.

[0103] Step (3) is the same as in Example 1.

[0104] Step (4) is the same as in Example 1, to obtain a UiO-66 (DB18C6)@ZIF-8 nanofiltration membrane with low crown ether content.

[0105] Comparative Example 8

[0106] This comparative example provides a method for preparing a UiO-66(DB18C6)@ZIF-8 nanofiltration membrane with a high content of crown ether.

[0107] Step (1) is the same as in Example 1.

[0108] In step (2), DB18C6 is replaced with a high molar amount of DB18C6 (2.16 g), and the other conditions are the same as in Example 1.

[0109] Step (3) is the same as in Example 1.

[0110] Step (4) is the same as in Example 1, to obtain a UiO-66 (DB18C6)@ZIF-8 nanofiltration membrane with high crown ether content.

[0111] Based on the test results of the above embodiments and comparative examples, the MOF-on-MOF nanofiltration membrane based on crown ether modified MOF channels described in this invention has been systematically evaluated through material structure characterization, separation performance testing, and ion selectivity testing.

[0112] Figure 1 The image shown is a transverse scanning electron microscope image of the process of preparing UiO-66 (DB18C6) in Example 1. The results show that the film surface exhibits a uniform octahedral MOF crystal structure, indicating that the MOF-A layer is well crystallized and completely covered on the seed layer.

[0113] Figure 2 The image shows a longitudinal scanning electron microscope (SEM) image of the UiO-66(DB18C6)@ZIF-8 nanofiltration membrane prepared in Example 1. The results show that two different MOF structures can be clearly observed, and the interface between the two layers is distinct, proving that the MOF-on-MOF composite structure has been successfully constructed.

[0114] Figure 3 The XRD spectra of UiO-66 (DB18C6) and UiO-66 are shown. The results indicate that both exhibit characteristic diffraction peaks consistent with standard UiO-66, indicating that the insertion of crown ether DB18C6 did not change the crystal structure of UiO-66, and both MOF-A materials were successfully synthesized.

[0115] Figure 4 The XRD pattern of ZIF-8 shows that the synthesized ZIF-8 exhibits characteristic diffraction peaks consistent with standard ZIF-8, indicating that the MOF-B material was successfully synthesized.

[0116] Figure 5 XPS images of the process of preparing UiO-66 (DB18C6) in Example 1 show Zr3d 5 / 2 ~182.5eV, Zr3d3 / 2 ~184.9 eV, the difference between the two is 2.4 eV, and Zr3d 3 / 2 The peak area is approximately Zr3d 5 / 2 Two-thirds of the, conforming to Zr 4+ The typical valence state of UiO-66 (DB18C6) proves that UiO-66 (DB18C6) was successfully loaded onto the membrane.

[0117] Figure 6 XPS images of UiO-66(DB18C6)@ZIF-8 were prepared for Example 1 to observe Zn2p. 3 / 2 ~1021 eV (Zn-N coordination), Zn2p 1 / 2 The difference between the two (Zn-O coordination) is 23 eV, and Zn2p 1 / 2 The peak area is approximately Zn2p 3 / 2 Two-thirds of the, conforming to Zn 2+ The typical valence state of ZIF-8 proves that ZIF-8 was successfully loaded onto the membrane surface.

[0118] Figure 7 The ion desalination rate of the UiO-66(DB18C6)@ZIF-8 nanofiltration membrane prepared in Example 1 in a mixed system with the same valence states is given. Figure 8 The desalination rate of the UiO-66 (DB18C6)@ZIF-8 nanofiltration membrane prepared in Example 1 was measured in different valence state mixed systems. The specific testing method was as follows: using a four-electrode system and an H-type electrolytic cell, the prepared nanofiltration membrane was placed in the middle of the H-type electrolytic cell, with the MOF side facing the feed inlet. 80 ml of the mixed ion system solution to be tested was added to the feed inlet side, and a platinum wire electrode was inserted as the working electrode, and an Ag / AgCl electrode as the sensing electrode. 80 ml of deionized water was added to the outlet side, and a platinum wire electrode was inserted as the counter electrode, and an Ag / AgCl electrode as the reference electrode. The test range was then set to -0.2V to 0.2V. After 24 hours of testing, 50 ml of solution from each inlet / outlet was taken for ICP testing. The ion concentrations at the inlet / outlet were measured, and the rejection rate was calculated. The desalination rate relationship is: R = (1- ) × 100%; where C PS C represents the ion concentration at the discharge port. FS This represents the ion concentration at the feed inlet.

[0119] Figure 7 The results show that the nanofiltration membrane of the present invention has a high rejection rate for monovalent metal cations in a mixed system of the same valence, and the competitive rejection between ions of the same valence does not affect the crown ether's ability to recognize the target ion. Figure 8The results show that the nanofiltration membrane of the present invention achieves a rejection rate of over 99% for divalent metal cations and over 95% for monovalent metal cations, verifying the effectiveness of the "two-first-one" cascade rejection mechanism synergistically achieved by the MOF-B layer and the crown ether modified MOF-A layer in mixed systems of different valence states.

[0120] Figure 9 The thermogravimetric curves of UiO-66 (DB18C6), UiO-66, and DB18C6 are shown. The results indicate that the MOF material doped with DB18C6 has a significantly smaller remaining mass after thermal weight loss than UiO-66 without crown ether, and the weight loss range coincides with the thermal decomposition temperature range of DB18C6, proving that the crown ether molecules have been successfully embedded in the MOF-A channels.

[0121] Figure 10 The BET adsorption-desorption curves of UiO-66 (DB18C6) and UiO-66 are shown. The results indicate that the specific surface area of ​​the MOF material is significantly reduced after the incorporation of DB18C6, indicating that the crown ether molecules occupy part of the space in the MOF-A channels, further verifying the successful intercalation of the crown ether.

[0122] Figure 11 The UiO-66(DB18C6)@ZIF-8 nanofiltration membrane prepared for Example 1 was used in K + / Na + IV curves in a mixed system.

[0123] Figure 12 The UiO-66(DB18C6)@ZIF-8 nanofiltration membrane prepared in Example 1 was used in Li + / Na + IV curves in a mixed system.

[0124] Figure 13 The UiO-66(DB18C6)@ZIF-8 nanofiltration membrane prepared in Example 1 was used in Li + / Mg 2+ IV curves in a mixed system.

[0125] Figure 14 The UiO-66(DB18C6)@ZIF-8 nanofiltration membrane prepared for Example 1 was used in Na + / Mg 2+ IV curves in a mixed system.

[0126] Figure 15 The UiO-66(DB18C6)@ZIF-8 nanofiltration membrane prepared for Example 1 was used in K + / Mg 2+ IV curves in a mixed system.

[0127] Figure 16 The UiO-66(DB18C6)@ZIF-8 nanofiltration membrane prepared for Example 1 was used in K + / Ca 2+ IV curves in a mixed system.

[0128] Figures 11-16 Both indicate that ions on the inlet side are continuously moving towards the outlet.

[0129] The separation performance of nanofiltration membranes prepared in Examples 1-6 and Comparative Examples 1-8 was tested under the same conditions as in Example 1. Only the K / Na ion system and the Li / Mg ion system were tested for comparison. The test results are shown in Table 1.

[0130] Table 1. Retention rates of nanofiltration membranes prepared in Examples 1-6 and Comparative Examples 1-8 for different metal cations.

[0131] The results of Examples 1-6 show that different crown ethers have different retention capacities for different monovalent metal cations. Different crown ether types (DB18C6, B12C4, B18C6, 18C6) can all prepare structurally complete MOF-on-MOF nanofiltration membranes, indicating that the method of the present invention has wide applicability to raw materials and adaptability to the process window.

[0132] The results of Comparative Examples 1-8 show that, without the addition of crown ether, there is a high rejection rate only for divalent metal cations, while the rejection rate for monovalent metal cations is poor, indicating that the intercalation of crown ether plays a key role in the selective rejection of monovalent metal cations. The rejection performance of the single MOF layer structure is significantly lower than that of the bilayer MOF-on-MOF structure, verifying the effectiveness of the "two-first-then-one" cascade rejection mechanism. The double deposition of each MOF layer helps to reduce crystal defects and ensure the continuity and integrity of the membrane layer. Too low a crown ether content is not conducive to the optimization of membrane separation performance. When the crown ether content is too high, although the rejection rate still maintains a high level, the improvement is limited compared with Example 1, while the cost of crown ether raw materials increases several times. Considering both performance and cost, the crown ether feed amount needs to be controlled within a reasonable range.

[0133] In summary, the MOF-on-MOF nanofiltration membrane based on crown ether modified MOF channels described in this invention has achieved the expected technical effects in terms of structural design, preparation process and separation performance, and has significant practicality and application value.

[0134] The embodiments described above are some, but not all, of the embodiments of the present invention. The detailed description of the embodiments of the present invention is not intended to limit the scope of the claimed invention, but merely to illustrate selected embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without inventive effort are within the scope of protection of the present invention.

Claims

1. A nanofiltration membrane based on crown ether-modified MOF pores, characterized in that, The nanofiltration membrane comprises: Alumina film substrate; A seed layer is disposed on the surface of the alumina film substrate; The MOF-A layer disposed on the surface of the seed layer is composed of a high-valence metal compound and a first organic ligand, and crown ether molecules are embedded in the pores of the MOF-A layer. The MOF-B layer is disposed on the surface of the MOF-A layer, and the MOF-B layer is composed of a low-valence metal compound and a second organic ligand.

2. The nanofiltration membrane according to claim 1, characterized in that, The thickness of the seed layer is 1~3 μm, the thickness of the MOF-A layer is 4~10 μm, and the thickness of the MOF-B layer is 3~6 μm.

3. The nanofiltration membrane according to claim 1, characterized in that, The high-valence metal compounds include one or more of zirconium n-propoxide, zirconium nitrate, zirconium chloride, titanium chloride, hafnium tetrachloride, zirconium acetylacetonate, titanium isopropoxide, titanium tetramethoxy, and hafnium dichloride; the low-valence metal compounds include one or more of zinc nitrate, cobalt nitrate, nickel nitrate, copper nitrate, iron nitrate, zinc chloride, cobalt chloride, nickel chloride, copper chloride, iron chloride, zinc acetylacetonate, cobalt acetylacetonate, nickel acetylacetonate, copper acetylacetonate, and iron acetylacetonate.

4. The nanofiltration membrane according to claim 1, characterized in that, The first organic ligand includes one or more of benzoic acid, o-methylbenzoic acid, m-methylbenzoic acid, p-methylbenzoic acid, phthalic acid, isophthalic acid, terephthalic acid, o-ethylbenzoic acid, m-ethylbenzoic acid, p-ethylbenzoic acid, 2-aminoterephthalic acid, and 2-amino-1,4-phthalic acid; the second organic ligand includes one or more of imidazole, 1-methylimidazolium, 2-methylimidazolium, 4-methylimidazolium, 1,2-dimethylimidazolium, benzimidazole, 2-methylbenzimidazole, and 2-phenylbenzimidazole.

5. The nanofiltration membrane according to claim 1, characterized in that, The crown ethers include one or more of 12-crown-4, 15-crown-5, 18-crown-6, 24-crown-8, benzo-12-crown-4, benzo-15-crown-5, benzo-18-crown-6, benzo-21-crown-7, dibenzo-15-crown-5, dibenzo-18-crown-6, dibenzo-21-crown-7, dibenzo-24-crown-8, dibenzo-30-crown-10, 4-carboxybenzo-15-crown-5, and 4-carboxybenzo-18-crown-6.

6. A method for preparing a nanofiltration membrane based on crown ether-modified MOF pores as described in any one of claims 1 to 5, characterized in that, Includes the following steps: S1. The alumina film is placed in an N,N-dimethylformamide solution containing the first organic ligand for pretreatment to form a seed layer on the surface of the alumina film. S2. Mix and dissolve the high-valence metal compound, the first organic ligand and the crown ether, and grow it in situ on the surface of the alumina film treated by S1 to deposit the MOF-A layer and make the crown ether molecules synchronously embedded in the pores of the MOF-A layer. S3. Repeat step S2 once to complete the secondary deposition of the MOF-A layer and the secondary intercalation of the crown ether; S4. Mix and dissolve the low-valence metal compound with the second organic ligand, and deposit a MOF-B layer on the surface of the film obtained in S3; S5. Repeat step S4 once to complete the secondary deposition of the MOF-B layer and obtain the nanofiltration membrane based on crown ether modified MOF channels.

7. The preparation method according to claim 6, characterized in that, In step S2, the mass ratio of the high-valence metal compound, the first organic ligand, and the crown ether is 1:(1-3):(1.8-5).

8. The preparation method according to claim 6, characterized in that, In step S2, the deposition temperature is 25~35 ℃ and the deposition time is 12~24 h; in step S4, the deposition temperature is 25~35 ℃ and the deposition time is 1~2 h.

9. The preparation method according to claim 6, characterized in that, In step S1, the pretreatment temperature is 110~140℃ and the pretreatment time is 1~3 h.

10. The use of a nanofiltration membrane as described in any one of claims 1 to 5 in separating a mixed liquid containing monovalent metal cations and divalent metal cations.